New directions in information technology law: learning from human–computer interaction - Urquhart, Lachlan; Rodden, Tom (Taylor and Francis, 2017)
Effectively regulating the domestic Internet of Things (IoT) requires a turn to technology design. However, the role of designers as regulators still needs to be situated. By drawing on a specific domain of technology design, human–computer interaction (HCI), we unpack what an HCI-led approach can offer IT law. By reframing the three prominent design concepts of provenance, affordances and trajectories, we offer new perspectives on the regulatory challenges of the domestic IoT. Our HCI concepts orientate us towards the social context of technology. We argue that novel regulatory strategies can emerge through a better understanding of the relationships and interactions between designers, end users and technology. Accordingly, closer future alignment of IT law and HCI approaches is necessary for effective regulation of emerging technologies.